Impact of intervention on breastfeeding outcomes and determinants based on theory of planned behavior. Issue 2 (April 2017) - Zhu, Yu; Zhang, Zhihong; Ling, Yun; Wan, Hongwei
Abstract: Background: Breastfeeding knowledge, attitude, subjective norm, and perceived control are significant determinants of breastfeeding, according to the theory of planned behavior (TPB). However, evidence concerning the effectiveness of the TPB-based intervention in breastfeeding promotion is sparse. Meanwhile, the changes of these determinants with time have not been examined in previous studies. Aim: To investigate the effectiveness of the TPB-based intervention program in improving exclusive breastfeeding, and the interaction of time and intervention on these determinants of breastfeeding. Methods: 285 primiparous mothers were included, with 157 mothers in the experimental group and 128 mothers in the control group. The experimental group received the TPB-based intervention program delivered during 6 weeks postpartum, while both the experimental and control groups received the standard obstetric care. Findings: Scores of breastfeeding knowledge, attitude and breastfeeding control increased with time from baseline to 6 weeks postpartum, while breastfeeding subjective norm decreased at 6 weeks both in the experimental and the control groups. Besides, scores of the four determinants were significantly higher in the experimental group than these in the control group at 3 days and 6 weeks, except for breastfeeding control at 6 weeks, which resulted in the higher exclusive breastfeeding rates at 3 days and 6 weeks in the experimental group than the control group. Discussion and conclusions: The TPB-based intervention was effective in promoting exclusive breastfeeding during 6 weeks postpartum. Future interventions are recommended to adjust intervention strategies with time, and give more focus on providing continued breastfeeding support after discharge.